2012
DOI: 10.1128/aem.07912-11
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Polymyxin in the Surrogate Host Bacillus subtilis by Introducing a Foreign ectB Gene and Disrupting the abrB Gene

Abstract: ABSTRACTIn our previous study,Bacillus subtilisstrain BSK3S, containing a polymyxin biosynthetic gene cluster fromPaenibacillus polymyxa, could produce polymyxin only in the presence of exogenously addedl-2,4-diaminobutyric acid (Dab). The dependence of polymyxin production on exogenous Dab was removed by introducing an Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 32 publications
(29 reference statements)
0
33
0
Order By: Relevance
“…This would make sense given that they are both the polymyxins and octapeptins are produced by closely related Bacillus spp . 62, 63 In line with this theory, the aforementioned mode of action studies suggest that octapeptins have retained the polymyxin-like ability to bind to lipid A (a Gram-negative specific outer membrane component), whilst having developed the extra ability to bind to bacterial phospholipids, which endows them with a broader spectrum of activity against Gram-positives and yeast.…”
Section: Biosynthesismentioning
confidence: 88%
See 1 more Smart Citation
“…This would make sense given that they are both the polymyxins and octapeptins are produced by closely related Bacillus spp . 62, 63 In line with this theory, the aforementioned mode of action studies suggest that octapeptins have retained the polymyxin-like ability to bind to lipid A (a Gram-negative specific outer membrane component), whilst having developed the extra ability to bind to bacterial phospholipids, which endows them with a broader spectrum of activity against Gram-positives and yeast.…”
Section: Biosynthesismentioning
confidence: 88%
“…It is tenable to imagine that in order to achieve killing of polymyxin-resistant Gram-negative and Gram-positive bacteria which were competing for nutrients in its environment, Bacillus circulans has evolved the octapeptin core scaffold through module swapping and deletion events of its nonribosomal biosynthetic machinery. 62, 63 Whereas, the polymyxin producing Bacillus polymyxa may not have encountered Gram-positive competition, and hence did not have a need to diversify the polymyxin core scaffold to increase its antimicrobial spectrum beyond Gram-negatives. This would make sense given that they are both the polymyxins and octapeptins are produced by closely related Bacillus spp .…”
Section: Biosynthesismentioning
confidence: 99%
“…It is necessary to propose nonlinear NRPS biosynthetic models that can further unravel the details of this biosynthetic mechanism. The Gram-positive bacterium B. subtilis serves as a model organism and is intensively used in the heterologous expression of commercial metabolites (30)(31)(32). However, apart from the present study, no nonlinear NRPS assembly line has been observed in this well-characterized species.…”
mentioning
confidence: 65%
“…However, as a metabolite, surfactin synthesis is regulated by several global transcription genes, and these genes also regulate other gene’s expression. For example, AbrB gene encodes a repressor that controls the expression of genes involved in sporulation (Robertson et al, 1989) and the production of antibiotics (Park et al, 2012). Jung et al (2012) reported that surfactin production can be improved by activating two competence-stimulating pheromones, ComX and the competence and sporulation factor, to stimulate the transcription of srfA operon.…”
Section: Discussionmentioning
confidence: 99%